Carpal Tunnel Syndrome as a Test Case for Value Assessment During the Presurgical Period: The Impact of Structure and Processes of Care. Issue 1 (3rd January 2023) - Sears, Erika D.; Evans, Richard; Burns, Jennifer; Chung, Kevin C.; Hayward, Rodney A.; Kerr, Eve A.
Abstract : Background: Few performance measures assess presurgical value (quality and utilization). Objectives: Using carpal tunnel syndrome (CTS) as a case study: (1) develop a model to evaluate presurgical quality and utilization and (2) identify opportunities for value improvement. Research Design: A retrospective cohort study utilizing Veterans Affairs (VA) national administrative data. Subjects: Patients who were evaluated in a VA primary care clinic on at least 1 occasion for CTS and received carpal tunnel release over a 7-year period. Measures: We modeled facility-level performance on 2 outcomes: surgical delay (marker of quality) and number of presurgical encounters (utilization) for CTS, and examined association between patient, facility, and care process variables and performance. Results: Among 41, 912 Veterans undergoing carpal tunnel release at 127 VA medical centers, the median facility-level predicted probability of surgical delay was 48%, with 16 (13%) facilities having significantly less delay than the median and 13 (10%) facilities having greater delay. The median facility-level predicted number of presurgical encounters was 8.8 visits, with 22 (17%) facilities having significantly fewer encounters and 22 (17%) facilities having more. Care processes had a stronger association with both outcomes than structural variables included in the models. Processes associated with the greatest deviations in predicted delay and utilization included receipt of repeat electrodiagnostic testing, use of 2 or more nonoperative treatments, and community referral outside of VA. Conclusions: Using CTS as a test case, this study demonstrates the potential to assess presurgical value and identify modifiable care processes associated with presurgical delay and utilization performance.